A survey from UAV in critical areas: the advantages of technology in areas with complex terrain - Baglione, Zaira (GEOmedia, 2016)
The tale of two experiences in the geological and cultural heritage area through the use of fixed-wing drones. Innovation and high quality of the data returned from an aero-photogrammetric survey as support to the activities of the different professionals. From the survey phase to the post-production all the precautions to obtain images with a very good resolution and solve obstacles for the mapping of areas not easily accessible such as quarries.